Pleomorphic adenoma in jugal mucosa: case report (Research, Society and Development, 2021)
Objective: Highlight the diagnostic relevance in clinical dental practice, seeking the correct approach in the treatment of pleomorphic adenoma in the region of the buccal mucosa, as well as discussing the pathogenesis of the lesion. Case details: Male patient, 64 years old, attended the Dental School Clinic complaining of an asymptomatic lesion that appeared slowly approximately 8 months ago. The intraoral examination revealed a single nodular lesion in the buccal mucosa, white, reddish and yellowish in color, smooth, well-delimited, oval-shaped and firm consistency. The diagnosis hypothesis was lipoma. We opted for excisional biopsy to confirm the lesion through anatomopathological study. Final considerations: The performance of biopsy is essential in order to rule out other diagnostic hypotheses. It is important that the dental surgeon has technical training to propose the most appropriate treatment, restoring the patient's well-being, self-esteem and health, while maintaining a satisfactory prognosis.